Antimicrobial Activity of Soil Clostridium Enriched Conditioned Media Against Bacillus mycoides, Bacillus cereus, and Pseudomonas aeruginosa - Pahalagedara, Amila Srilal Nawarathna Weligala; Flint, Steve; Palmer, Jon; Subbaraj, Arvind; Brightwell, Gale; Gupta, Tanushree Barua (Frontiers in Microbiology, 2020)
The rise of antimicrobial resistant bacteria has fast-tracked the exploration for novel antimicrobial compounds. Our knowledge on antimicrobial producing soil anaerobes such as Clostridium spp. is very limited. In the present study, the antimicrobial activity of soil Clostridium enriched conditioned/spent media (CMs) against Bacillus mycoides, Bacillus cereus and Pseudomonas aeruginosa was assessed by turbidimetric growth inhibition assay. Our results highlighted antimicrobial potential of soil Clostridium enriched conditioned media against pathogenic and spoilage bacteria. Farm 4 soil conditioned medium (F4SCM) demonstrated a greater growth inhibition activity against all three tested microorganisms in comparison to other soil conditioned media. Non-targeted metabolite profiling of all soil conditioned media revealed distinctive polar and intermediate-polar metabolites in F4SCM, consistent with its strong antimicrobial property. Moreover, 539 significantly abundant metabolites including some unique features were detected in F4SCM suggesting its substantial and specialized chemical diversity. This study putatively identified seven significantly high metabolites in F4SCM; 3-hydroxyphenylacetic acid, γ-aminobutryic acid, creatine, tryptamine and 2-hydroxyisocaproic acid. Tryptamine and 2-hydroxyisocaproic acid were previously reported to have antimicrobial properties. The present study shows that soil Clostridium spp. are a promising group of bacteria producing metabolites with antimicrobial activity and provide future prospects for clostridial antimicrobial discovery within their metabolic diversity.